(3EHQGR dWGFa GdZhGeV hEMQGR UfGYI GdaQGFVs - (3CHhGdYHGS CMeO Hf GdeLOi GdTGaYjs; (3CMeO Hf GdeLOj GdTGaYj, CHh GdYHGSs ((3fSN s)
(3ChdgG (B:s
(3CeG HYO agPG eNUQ dNUJg ef cJGHi GdehShe HGdcGai ai ehGQjK GdCeI s
(3BNQgG (B:s
(3hEfeG PcQfG gPg GdeSCdI GdebUhO ef GdCYJQGV djdG jba CMO cdGeg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Yde GdaQGFVs